Explain how to determine the inverse of the function \( f(x) = 2x + 3 \) and demonstrate by finding its graph.
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To determine the inverse of the function \( f(x) = 2x + 3 \), start by replacing \( f(x) \) with \( y \), giving you the equation \( y = 2x + 3 \). Next, swap \( x \) and \( y \) to find the inverse: \( x = 2y + 3 \). Now, solve for \( y \): \( 2y = x - 3 \) leads to \( y = \frac{x - 3}{2} \). Thus, the inverse function is \( f^{-1}(x) = \frac{x - 3}{2} \). For the graph, plot both functions on the same coordinate plane. The original function \( f(x) \) will be a straight line with a slope of 2, while the inverse function \( f^{-1}(x) \) will also be a straight line with a slope of 0.5. They will reflect over the line \( y = x \), showcasing their inverse relationship in a visually appealing way!